Some Effects of Trypsin and Streptokinase on Platelet Aggregation - Wilson, Patricia A; McNicol, G. P; Douglas, A. S (Thrombosis and Haemostasis, 1967)
The effect of the proteolytic enzymes trypsin and streptokinase on platelet aggregation were investigated using the turbidimetric system of Born and the Chandler tube system. The following results were obtained :1. ADP and adenosine display a similar action in the Chandler tube system as in the turbidimetric system.2. Platelet aggregation is accelerated in the Chandler tube system by trypsin over a range of concentrations 10 µg/ml to 1 mg/ml and in the turbidimetric system over a range of concentrations 100 µg/ml to 1 mg/ml.3. Streptokinase, at low concentrations, enhances aggregation in the Chandler tube system but plasma antiplasmin must be destroyed before a similar effect is observed in the turbidimetric system.4. The results obtained with trypsin cannot be accounted for solely on the basis of its coagulant action.